Turismo e governança: os agentes sociais e as relações existentes na Floresta Nacional do Tapajós – Pará/Amazônia - HAMOY, Juliana Azevedo (Universidade Federal do Pará, 2023)
This study addresses the theme of tourism in Conservation Units and governance in the management process, whose research locus are the communities the Jamaraquá, Maguari, and São Domingos, located in the Tapajós National Forest (FLONA) in western Pará, Brazil. The general objective of this study is to analyze the relationships between different actors in the tourism chain in FLONA Tapajós, examining governance and collective action of local social agents. For this purpose, four specific objectives were identified: 1) Identify and analyze actors involved in tourism in FLONA Tapajós; 2) Analyze tourism governance in the studied FLONA; 3) Verify the existence of collective actions in the communities and their governance process; and 4) Analyze how local communities are involved in this management process. The research was built upon qualitative data and an interdisciplinary approach, using bibliographic references on tourism, governance, collective action, and environmental issues. Documentary research was also conducted, along with data collection through semi-structured interviews with agents identified as active in the field of tourism relations in FLONA Tapajós. The results indicate that the existing collective action in the communities, resulting from a process of conflict and resistance for the right to remain, has significantly contributed to the organization of collective action to achieve common objectives regarding the use of FLONA Tapajós for survival and supplementary income, such as forest management and tourism. However, concerning tourism, collective action is limited in terms of its tourism potential. The relationships are interconnected, when one of the actors reduces their influence, the entire field is negatively affected. This makes possible to state that if there were a significant influence from tourism management agencies towards and residents involved in tourism in FLONA Tapajós, the structure, service delivery, information, promotion, and overall service quality could be improved.